High-risk surgical stage 1 endometrial cancer: analysis of treatment outcome - Fogaroli Ricardo C; Novaes Paulo E; De Melo Marcel D; Pellizzon Antonio C; Patia Barbara F; Viani Gustavo A; Conte Maria A; Salvajoli Joao V (Radiation Oncology, 2006)
Abstract Purpose To report the relapse and survival rates associated to treatment for patients with stage IC, grade 2 or grade 3 and IB grade 3 diseases considered high risk patients group for relapse. Materials and methods From January 1993 to December 2003, 106 patients with endometrial cancer stage I were managed surgically in our institution. Based on data from the medical records, 106 patients with epithelial endometrial cancer met the following inclusion criteria: stage IC grade 2 or 3 and IB grade 3 with or without lymphovascular invasion. Staging was defined according to the FIGO surgical staging system. Postoperative adjuvant radiotherapy consisted of external beam pelvic radiation, vaginal brachytherapy alone or both. The median age was 65 years (range, 32–83 years), lymph node dissection was performed in 45 patients (42.5%) and 14 patients (13.2%) received vaginal brachytherapy only, and 92 (86.8%) received combined vaginal brachytherapy and external beam radiotherapy. The median dose of external beam radiotherapy administered to the pelvis was 4500 cGy (range 4000 – 5040). The median dose to vaginal surface was 2400 cGy (range 2000 – 3000). Predominant pathological stage and histological grade were IC (73.6%) and grade 3 (51.9%). The lymphovascular invasion was present in 33 patients (31.1%) and pathological stage IC grade 2 was most common (48. 1%) combination of risk factors in this group. Results With a follow up median of 58.3 months (range 12.8 – 154), five year overall survival and event free survival were 78.5% and 72.4%, respectively. Locoregional control in five year was 92.4%. Prognostic factors related with survival in univariate analyses were: lymphadenectomy (p = 0.045), lymphovascular invasion (p = 0.047) and initial failure site (p < 0.0001). In multivariate analyses the initial failure in distant sites (p < 0.0001) was the only factor associated with poor survival. Acute and chronic gastrointestinal and genitourinary toxicity grades 3 were not observed. Conclusion In conclusion, our results showed that the stage IC, grade 2, 3 and IB grade 3 endometrial cancer was associated with significantly increased risk of distant relapse and endometrial carcinoma-related death independently of salvage treatment modality.